The effect of calcium channel blockers on the outcome of acute myeloid leukemia. Issue 12 (December 2014) - Chae, Young Kwang; Dimou, Anastasios; Pierce, Sherry; Kantarjian, Hagop; Andreeff, Michael
Abstract The effect of calcium channel blockers (CCBs), beta blockers and angiotensin converting enzyme (ACE) inhibitors or angiotensin receptor blockers (ARBs) on the prognosis of patients with acute myeloid leukemia (AML) is largely unknown. We collected data on the use of these medications in 1043 patients with AML, excluding promyelocytic leukemia, diagnosed and treated at M. D. Anderson Cancer Center between 2000 and 2012. Treatment with either amlodipine or diltiazem predicted a worse overall survival (hazard ratio [HR] 1.6, 95% confidence interval [CI] 1.22–2.06, p < 0.0001). There was no difference in survival depending on whether patients were taking beta blockers, ACE inhibitors or ARBs. The effect of CCBs on survival was independent from the National Comprehensive Cancer Network risk classification, age, performance status, response to treatment, year of diagnosis and CD34 levels, assessed by flow cytometry (HR 1.39, 95% CI 1.05–1.80, p = 0.02). Treatment with either amlodipine or diltiazem predicts worse survival in patients with AML independent of known prognostic factors.